2018
DOI: 10.3390/toxins10010038
|View full text |Cite
|
Sign up to set email alerts
|

Updated Overview of Infrared Spectroscopy Methods for Detecting Mycotoxins on Cereals (Corn, Wheat, and Barley)

Abstract: Each year, mycotoxins cause economic losses of several billion US dollars worldwide. Consequently, methods must be developed, for producers and cereal manufacturers, to detect these toxins and to comply with regulations. Chromatographic reference methods are time consuming and costly. Thus, alternative methods such as infrared spectroscopy are being increasingly developed to provide simple, rapid, and nondestructive methods to detect mycotoxins. This article reviews research conducted over the last eight years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 66 publications
(101 reference statements)
0
43
0
1
Order By: Relevance
“…All were selected by the UVE algorithm and were distributed throughout the spectrum. The growth of the microorganism is accompanied by the consumption of various nutrients in the peanuts, such as starch, proteins, fats, sugars, vitamins, and water, so the absorption wavelengths of the reactive nutrients may also play a role in TMC prediction . It therefore makes sense that more wavelengths selected by the UVE algorithm are related to the prediction of the TMC directly or indirectly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All were selected by the UVE algorithm and were distributed throughout the spectrum. The growth of the microorganism is accompanied by the consumption of various nutrients in the peanuts, such as starch, proteins, fats, sugars, vitamins, and water, so the absorption wavelengths of the reactive nutrients may also play a role in TMC prediction . It therefore makes sense that more wavelengths selected by the UVE algorithm are related to the prediction of the TMC directly or indirectly.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly used to detect mycotoxins in maize, wheat, and barley. Qualitative prediction is more feasible than quantitative prediction . Fernandez‐Ibanez et al .…”
Section: Introductionmentioning
confidence: 97%
“…Several papers have addressed the use of FTNIR spectroscopy as an indirect analytical tool for the quantitative analysis of DON in cereals; however, most of them showed that FTNIR spectroscopy is only of limited applicability in the quantitative determination of DON in cereals …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in two recent overviews on IR methods for the analysis of mycotoxins in cereals it was clearly evident that the majority of referenced papers focused on DON followed by fumonisins, aflatoxins, zearalenone, ochratoxin A, and nivalenol, while the most investigated matrices were maize and wheat. Furthermore, most applications of IR for mycotoxin analysis in these commodities were based on the NIR spectral range …”
Section: Introductionmentioning
confidence: 99%
“…Data exploration allows finding sample groups, the relation between variables and management with outliers samples by means of a PCA or a parallel factor analysis (PARAFAC) (Bro, ; Rodrigues, Condino, Pinheiro, & Nunes, ). Data preprocessing can be handled with preprocessing algorithms, such as smoothing methods (Savitzky–Golay, Gaussian filter, median filter, moving average), normalization and scaling, detrending (Levasseur‐garcia, ), 1 st Derivate, 2 nd Derivate–Savitzky Golay (Savitzky & Golay, ), Standard Normal Variation (Teye, Uhomoibhi, & Wang, ), Orthogonal Signal Correction (Wold, Antti, Lindgren, & Öhman, ), and Multiple Scatter Correction to build and enhance calibration models (Su & Sun, ). The selected preprocessing method can be related to data features to, for example, rid up multiplicative and additive effects in spectra.…”
Section: Fast Nondestructive Technologies Applied In the Cocoa Industrymentioning
confidence: 99%